2012
DOI: 10.1007/s00345-012-0841-1
|View full text |Cite
|
Sign up to set email alerts
|

A switch from GnRH agonist to GnRH antagonist in castration-resistant prostate cancer patients leads to a low response rate on PSA

Abstract: Switch from an agonist to an antagonist of GnRH has a limited impact on PSA at 3 months in castration-resistant prostate cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…The rate of patients who reached this 50 % value in our study was better compared with that in a previous study, in which only 5.8 % (one out of 17 patients) reached a 50 % PSA decrease [3]. This might be because of differences in the inclusion criteria.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The rate of patients who reached this 50 % value in our study was better compared with that in a previous study, in which only 5.8 % (one out of 17 patients) reached a 50 % PSA decrease [3]. This might be because of differences in the inclusion criteria.…”
Section: Discussioncontrasting
confidence: 69%
“…But another paper described that the switch from GnRH agonist to GnRH antagonist had a limited effect on the PSA level in CRPC patients [3]. We considered that it was essential to identify the efficacy of the switch and retrospectively examine its efficacy in prostate cancer patients with PSA failure after ADT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LH-RH antagonist may have contributed to the 56% decrease in PSA, from 1,235 to 540 ng/ml. Two previous studies indicated that switching from LH-RH agonist to LH-RH antagonist could decrease PSA levels in CRPC patients [5, 6]. Degarelix, which is a recently developed LH-RH antagonist, showed a significantly lower risk of PSA progression or death in a certain population when compared with the LH-RH agonist [7].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in effect between LH-RH agonist and antagonist could be explained by (1) a loss of testosterone surge or a reduction of testosterone, (2) the suppression of follicle-stimulating hormone and (3) a direct effect of the LH-RH antagonist on the LH-RH receptors in the prostate cancer cells [2]. A previous study indicated the possibility of a slight change in testosterone level being a cause of PSA decrease [5]. However, PSA levels in these previous studies were 3–60 ng/ml upon commencement of LH-RH antagonist administration [5, 6].…”
Section: Discussionmentioning
confidence: 99%